Development of a cold chain free DNA based rapid test for the early detection of methicillin-resistant staphylococcus aureus (MRSA) from clinical samples - Singh, Kirnpal Kaur Banga (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2010)
Methicillin-resistant Staphylococcus aureus strains are an increasing infection control problem in hospitals worldwide. Infection with MRSA strains is usually preceded by nasal colonization. Although some patients are admitted with MRSA colonization, others acquire MRSA during their hospital stay. The prevalence of MRSA nasal carrier differs widely among different countries including from one hospital to another in the same country. Early identification of patients colonized with MRSA and subsequent prevention of patient-to-patient spread through infection control measures are believed to be potent interventions to control MRSA. Nucleic acid-based tests using PCR are increasingly being used in laboratories to replace timeconsuming, labor-intensive and less sensitive conventional diagnostic methods such as biochemical identification and Kirby-Bauer antimicrobial susceptibility tests. The multiplex PCR assay was successfully used with nasal swab specimen to detect staphylococcal genus, species, PVL toxin and methicillin resistant genotypes within one day, thus penmit the same day identification and isolation of MRSA nasal carrier subjects. Due to lack of a rapid test which gives quick info on the detection of MRSA clinical isolates currently, the thermostabilized multiplex PCR assay developed in this study is extremely versatile. This assay is apparently more cost effective than conventional methods for the detection of MRSA. Specific primers were designed based on the conserved and non-conserved regions of the target genes used in the monoplex and multiplex PCR assays. The sizes of the 5 PCR products, including IC, were designed to obtain a staircase-like pattern when separated by agarose gel electrophoresis. A total of 5 primer pairs were designed using VectorNTI Advance 9 software (Invitrogen Corporation, California, USA). Out of those 5 pairs, one pair was designed to amplify a specific gene ofthe staphylococcus genus (16S rRNA gene). The ClustaiW interface in VectorNTI software was used to align all the downloaded sequences. The conserved and non-conserved regions of these alignments were visualized using GeneDoc software. Based on the conserved region on the alignment, a specific primer pair was designed to amplify the 16S rRNA while the non-conserved regions were used to design primer pairs for femA S. aureus, mecA, and lukS genes. The designed primers were BLAST analysed through GenBank for specificity (http://www.ncbi.nlm.nih.gov/BLAST/). Search results showed none of the designed primers had similarity with other non-specific gene; hence they were specific for their target genes. After successfully developing a complete multiplex PCR for the identification of MRSA with virulent toxin we went on thermostabilized the multiplex PCR reagents by freeze-drying in the presence of an enzyme stabilizer. In accelerated stability evaluation test it was found that the thermostabilized multiplex PCR mix was stable at 1 0°C for more than one year. The diagnostic accuracy of the thenmostabilized multiplex PCR at the genus level was determined using 231 nasal swabs and found to be 1 00% sensitive, specific, positive and negative predictive values for staphylococci isolates. The femA gene in the multiplex PCR assay was able to rule out non S. aureus staphylococci. The present study is believed to be the first to develop a combined molecular test for the rapid identification and discrimination of the Staphylococcus genus from others, with simultaneous discrimination of methicillin-resistant from susceptible staphylococcal strains, S. aureus from CoNS, and concomitant detection of PVL genes.